2022
DOI: 10.1093/eurpub/ckac140
|View full text |Cite
|
Sign up to set email alerts
|

Association of METS-IR with incident hypertension in non-overweight adults based on a cohort study in Northeastern China

Abstract: Background Insulin resistance (IR) plays an important role in the progression of hypertension (HTN); therefore, early identification of IR is clinically important for preventing HTN. Our study aims to explore the relationship between the metabolic score for IR (METS-IR) and HTN in Chinese population who maintained non-overweight. Methods A total of 4678 adults who underwent annual health check-up in our institution from 2010 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…4b, p for subgroup difference all > 0.05). Results of meta-analysis with METS-IR analyzed in continuous variables also showed that METS-IR was associated with the risk of hypertension (four datasets [26][27][28], RR for 1-unit increment of METS-IR: 1.15, 95 % CI: 1.08 to 1.23, p < 0.001, I 2 = 79 %; ▶ Fig. 5).…”
Section: Meta-analysis Resultsmentioning
confidence: 74%
See 4 more Smart Citations
“…4b, p for subgroup difference all > 0.05). Results of meta-analysis with METS-IR analyzed in continuous variables also showed that METS-IR was associated with the risk of hypertension (four datasets [26][27][28], RR for 1-unit increment of METS-IR: 1.15, 95 % CI: 1.08 to 1.23, p < 0.001, I 2 = 79 %; ▶ Fig. 5).…”
Section: Meta-analysis Resultsmentioning
confidence: 74%
“…As shown in Table 1 , eight observational studies, including two cohort studies 21 28 and six cross-sectional studies 22 23 24 25 26 27 , were included in the meta-analysis. These studies were published between 2019 and 2022, and performed in Mexico 21 , China 22 23 24 25 , 27 28 , and Japan 26 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations